Teaching science communication in high school and university through a genre-based approach - Любашенко, Олеся Вадимівна; Лоза, Владислава; Горкуненко, Алла (Київський національний університет імені Тараса Шевченка, 2024)
Background. In the last decade, the focus has been on improving science communication when presenting research results or teaching specific topics in school and university programs through student participation. A genre-based approach has been employed in both oral and written forms. In the context of educational reforms in Ukraine, secondary schools are actively adopting innovative teaching methodologies to provide students with a comprehensive scientific education. Undoubtedly, these advancements call for improvements in students' science communication skills. The objective of this paper is to present and discuss the outcomes of integrating science communication training in the genre of scientific presentation as part of the curriculum in high specialised schools and universities. The framework suggests employing Ukrainian language instruction based on a genre approach using a model developed by the authors. Method. The study was conducted based on the methodological principles outlined by Norman Wallen and Jack Fraenkel (2013). The empirical phase took place from January to April 2024, involving two 10th-grade students at Specialized School 277 of Kyiv. A total of 17 learners voluntarily participated in the experimental training. Additionally, 14 fourth-year bachelor's students from Taras Shevchenko National University of Kyiv, specialising in "Theory and Methodology of Teaching Ukrainian and Foreign Languages and Literature in Secondary School," participated in a final survey. The survey was conducted with the consent of the school and university students and did not impact their grades in any subjects. It was carried out in classrooms to mitigate external influences on the results. Results and discussion. The instructional methodology for enhancing students' science communication skills is implemented in four stages: 1) acquainting students with the features of scientific language style of in Ukrainian and the genre of scientific reporting as well as facilitating mastery of scientific terminology, phraseology, and metaphors; 2) providing guidance for the preparation of a scientific report in oral and written forms; 3) analysis of procedural, linguistic, and textual characteristics of science communication; 4) engaging students in a collective presentation and discussion of a scientific report. After the experimental training, roughly 92% of students grasped the structure of scientific reporting, and about 78% acquired scientific vocabulary and the principles of scientific communication. The accuracy in identifying scientific genres approached that of university students, reaching 89% of the total participants. Following the experimental training, approximately 92% of students demonstrated comprehension of the structure of scientific reporting, with around 78% acquiring scientific vocabulary and developing an understanding of the principles of science communication. The accuracy in identifying scientific genres among the participants reached 89%, approaching that of university students.

У статті обґрунтовано жанровий підхід до формування компетентності в науковій комунікації в учнів і студентів у процесі навчання мови. Представлено оригінальну технологію навчання і викладено результати тренування наукової комунікації та оволодіння науковим стилем української мови в 10 класі старшої профільної школи. Навчальну технологію застосовано для вдосконалення усного і писемного мовлення учнів у жанрі наукової доповіді. Технологію запропоновано реалізовувати поетапно: 1) ознайомлення з особливостями наукового стилю української мови та жанру наукової доповіді; 2) інструкції до підготовки наукової доповіді в усній і писемній формах; 3) аналіз процесуальних, мовних і текстових характеристик наукової комунікації; 4) виголошення колективної наукової доповіді учнями та її обговорення. Навчальні досягнення учнів старшої профільної школи, виявленні у процесі експериментального навчання, зіставлено з компетентністю студентів-філологів університету в науковій комунікації та використанні жанру наукової доповіді. Зроблено висновок про доцільність навчання мови й опанування наукового стилю за умов системного тренування наукової комунікації учнів і студентів та цілісного оволодіння окремим жанром наукової комунікації в усній і писемній формах
Навчання наукової комунікації у старшій школі та університеті з позицій жанрового підходу
Keywords: educational technology; genre-based approach; scientific communication; genre of scientific presentation; language teaching; навчальна технологія; жанровий підхід; наукова комунікація; жанр наукової доповіді; навчання мови